Empirical study on synergy of China's rail freight transportation system. (24th November 2015) - Feng, Fenling; Liu, Haihong; Liu, Chengguang; Zhang, Jiaqi; Zhou, Hongwei
This article analyzes the characteristics of evaluating synergy of China's rail freight transportation system. According to Delphi method, an evaluation indicator system of synergy of the rail freight transportation system is established and the system is in accordance with railway development strategies and synergic targets. Besides, this article builds up an evaluating model for synergy of China's rail freight transportation system and conducts an empirical study with statistical data from 1995 to 2013. The results indicate that there is an increasing tendency toward the synergy degree of the railway freight system, with a slow growth before the year 2002, and then has a sustained and rapid growth until 2010 as the trends become smooth. The synergy degree of the rail freight transportation system in 2013 has increased nearly 34 times than 1996 from 0.016810995 to 0.57142183. This article concludes that indicators such as synergy in structure, transportation, organization, management, and information have made an outstanding contribution to the synergy degree of the rail freight transportation system.